Intra-abdominal hypertension in early post-kidney transplantation period is associated with impaired graft function. Issue 9 (17th July 2020) - Dupont, Vincent; Debrumetz, Alexandre; Leguillou, Adrien; Morland, David; Wynckel, Alain; Colosio, Charlotte; Mokri, Laetitia; Schvartz, Betoul; Vuiblet, Vincent; Larre, Stephane; Barbe, Coralie; Rieu, Philippe
Abstract: Background: Moderate hyperhydration is often achieved in the early post-kidney transplantation period. Whether this strategy could lead to the development of intra-abdominal hypertension (IAH) has never been assessed so far. We aimed to study the incidence of IAH after kidney transplantation and its association with graft function recovery. Methods: We conducted a prospective monocentric study among patients undergoing kidney transplantation at the University Hospital of Reims between May 2017 and April 2019. Intravesical pressure (IVP) was monitored every 8 h from Day 0 to 3. Results: A total of 107 patients were enrolled. Among 55 patients included in the analysis, 74.5% developed IAH. Body mass index >25 kg/m 2 was associated with IAH development {odds ratio [OR] 10.4 [95% confidence interval (CI) 2.0–52.9]; P   =   0.005}. A previous history of peritoneal dialysis was protective [OR 0.06 (95% CI 0.01–0.3); P   =   0.001]. IAH Grades III and IV occurred in 30.9% of patients and correlated with higher Day 3 creatininaemia (419.6   ±   258.5 versus 232.5   ±   189.4 μmol/L; P   =   0.02), higher delayed graft function incidence (41.2 versus 7.9%; P   =   0.04), lower Kirchner index measured using scintigraphy (0.47   ±   0.09 versus 0.64   ±   0.09; P   =   0.0005) and decreased Day 30 estimated glomerular filtration rate (35.8   ±   18.8 versus 52.5   ±   21.3, P   =   0.05). IAH patients had higher fluid balance (P   =   0.02). Evolution of IVP correlated with weight gain (P   <   0.01) and central venous pressure (P   <   0.001). Conclusions: IAH is frequent after kidney transplantation and IAH Grades III and IV are independently associated with impaired graft function. These results question current haemodynamic objectives and raise for the first time interest in intra-abdominal pressure monitoring in these patients. Clinical Trial Notation: ClinicalTrials.gov identifier: NCT03478176